Testing Northern Bobwhite Reintroduction Techniques in the Northern Edge of Their Range - William Macaluso; Christopher K. Williams; Theron M. Terhune II (National Quail Symposium Proceedings, 2017)
Pen-rearing young frequently fails as a reintroduction technique in game birds because of low postrelease survival rates in the wild. This may be caused by a combination of poor genetics from domestication, unhealthy birds, birds that do not exhibit wild behavior, or birds that are unfamiliar with their surroundings after hard releases. Recent research suggests that parent-rearing, involving pre- and posthatch imprinting of wild-strain northern bobwhite (Colinus virginianus) chicks by adults, may be a viable option for restoring populations. Imprinting potentially causes reintroduced birds to exhibit more natural behavior. We tested this method against a slightly modified traditional propagation tool (Surrogator®) with wild-strain birds. We conducted our research on a 170-ha property containing a mixture of early successional and hardwood habitat on Long Island, New York, during the summers of 2013 and 2014. We tested the effect of rearing methodology, mass at release (as a proxy for physical condition), release timing, and year on survival using Cox proportional hazard models. Hazard analysis revealed that only earlier release dates directly improved survival whereas treatment (parent-reared vs. Surrogator), body mass at release, and year did not affect survival. The methods tested on our study area did not result in 365-day survival rates high enough to re-establish quail in the area.
Keywords: Cox proportional hazards; foster parent; Long Island; New York; northern bobwhite; colinus virginianus; reintroduction; Surrogator; survival